Entre o silêncio dos pinhais e a solidão das paredes: a composição das personagens e sua relação com o espaço em Casa na duna, de Carlos de Oliveira - Hoffmann, Alana Francisca da Silva (2020)
In the mid-1930’s, Portugal was already under the regime of Estado Novo, a troubled period in which Portuguese Neorealism emerged, a literary movement influenced by certain Marxist conceptions and also by some American and Brazilian fiction of the 1930s. In the scope of the literary movement, Carlos de Oliveira occupies a central place among the authors whose work reflects a marked aesthetic concern. The neorealist theme of the decadence of the rural bourgeoisie and the consequent misery of the working class is evident in his first novel, Casa na Duna (1943), which inaugurates the so-called “tetralogy of gândara”, which includes the novels Pequenos Burgueses (1948), Uma Abelha na Chuva (1953) and Finisterra (1978). Casa na Duna follows the last three generations of the Paulos, a small bourgeoisie family who owns a farm in the village of Corrocovo. In this novel, the degradation, which initially seems restricted to socioeconomic aspects, can be also related to physical, moral, psychological and affective instances. In this sense, this dissertation is intended to understand, through the analysis of the composition of the characters along with the configuration of the space, the close relation between the collapse of the Paulo family and the ruin of their house. Therefore, we will especially focus on the formal and linguistic care with which the author constructs the fictional universe of gândara and the way in which its inhabitants are characterized. Moreover, we also observe how the author ideologically explores this fictional universe while avoiding to make the work merely an instrument of social criticism and worth of the aesthetic potentialities of the language.